Penghentian Penyidikan Oleh Kepolisian Dalam Penegakan Hukum Pidana Dengan Pendekatan Keadilan Restoratif (Studi Pada Kepolisian Daerah Aceh) - Ayub Dermawan; Rizkan Zulyandi; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The formulation of the problem in this study is related to regulation, the actualization of stopping investigations with a restorative justice approach at the Aceh Regional Police Office, and efforts to overcome obstacles to the application of restorative justice in the process of handling criminal cases from a legal perspective. The method used is empirical juridical research. Empirical juridical, namely a study that besides looking at positive legal aspects also looks at its application or practice in the field, in this case the approach is used to qualitatively analyze the termination of investigations with a restorative justice approach at the Aceh Regional Police Office. From the results of the study, the legal arrangements governing the termination of investigations using a restorative justice approach are regulated in Perpol 08 of 2021 which in practice contain formal and material requirements. The actualization of the application of stopping investigations with a restorative justice approach has been carried out 10 (ten) times at the Aceh Regional Police and has been running well in accordance with the internal rules of the police institution. Judging from the legal aspect, the Criminal Procedure Code does not regulate the termination of investigations on the grounds of restorative justice, so that it raises doubts for investigators in actualizing the termination of investigations with a restorative justice approach.